PENGENDALIAN KUALITAS PRODUK TAHU MENGGUNAKAN METODE SIX SIGMA DI UD. SUMBER URIP - Nina Hairiyah; Raden Rizki Amalia (AGROINTEK, 2020)
Tofu is one of the processed foods of the home industry which is processed from soybeans. One of the home industries that produce tofu in Tanah Laut Regency is UD. Sumber Urip. Currently the tofu products produced at  UD Sumber Urip have a non-uniform texture and size. It is necessary to analyze the application of quality control to the performance of tofu processing at UD  Sumber Urip. This research was conducted to control and improve the quality of tofu at  UD Sumber Urip by using the Six Sigma method through the Define, Measure, Analyze, Improve, and Control stages. Based on the results of the analysis of the sigma level of 1.87 and the value of  DPMO 626666. This shows that the company has not implemented the production process properly, because it is still far from the target 6σ. Based on this study it is recommended that companies should increase the quality of sigma by adjusting the size to the standard, paying attention to the addition of materials, providing a place to cut and paying attention to cleanliness in the tools used in the tofu industry process.